Development of phenylpropanoid sucrose esters as antidiabetic lead compounds - Ong, Li Lin (2019)
Alpha-glucosidase inhibitors (AGIs), particularly Acarbose, have received increased attention in the treatment of Type 2 diabetes (T2D) due to their effectiveness in managing postprandial blood glucose and associated macrovascular and microvascular health complications. However, AGIs are commonly plagued with side effects such as flatulence, diarrhoea and abdominal discomfort due to their strong inhibition of α-amylase. To overcome this, there is a need to seek new AGIs that either inhibit α-glucosidase alone or offer higher inhibition selectivity for α-glucosidase over α-amylase. This work focuses on the development of phenylpropanoid sucrose esters (PSEs) as potential AGIs that offer improved or comparable efficacy, but with reduced or complete eradication of side effects. A library of PSEs with variant structures needs to be synthesized in order to perform structure activity relationship (SAR) studies. As such, a defined synthetic strategy was developed so as to synthesize any structure we needed. The strategy starts with protecting sucrose with 2-methoxypropene to obtain 2,1’:4,6-di-O-isopropylidene sucrose which contains four free hydroxyl groups. With this compound, tetra-substituted PSEs can be synthesized. However, the four free hydroxyl groups possess similar reactivities which poses a challenge for the synthesis of mono-substituted PSEs due to lack of regioselectivity. Hence, we developed an orthogonal protection scheme using tert-butyldimethylsilyl (TBS), carboxybenzyl (Cbz), para-nitrobenzoyl (PNB) and levulinoyl (Lev) moieties to selectively protect 2,1’:4,6-di-O-isopropylidene sucrose. Following this strategy, a phenylpropanoid group can be selectively introduced at O-3, O-3’, O-4’and O-6’ to give four different series of mono-substituted PSEs. SAR studies of tetra-substituted and mono-substituted PSEs were conducted using in vitro α-glucosidase and α-amylase enzyme assays. From the studies, functional group(s) such as hydroxyl group, isopropylidene rings and the positions of the substituents at O-3, O-3’, O-4’ were identified as key structural features affecting the inhibitory activities. The in vitro findings allowed us to design and synthesize a PSE, Hybrid 1, which only inhibits α-glucosidase. Hybrid 1, alongside with 4CaS (PSE with ≥90% inhibtion for both enzymes), were selected for in vivo studies using a diet induced diabetic mouse model. Administration of these drugs orally via water showed controlled blood glucose levels following an intraperitoneal injection of 20% glucose solution in mice. Both PSEs are deemed to be as effective as standard drug Acarbose in reducing the surge in blood glucose after a glucose load in test mice. In addition, Hybrid 1 exhibited higher effectiveness in weight management as compared to 4CaS and Acarbose as well. Overall, this work has given us deep insight into the design and synthesis of PSEs and proved PSEs as effective AGIs. Moving forward, these synthesized lead compounds will be further evaluated to validate any common side-effects aforementioned.